2011
DOI: 10.1264/jsme2.me10202
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production Efficiency of an Anaerobic Hemicellulolytic Thermophilic Bacterium, Strain NTOU1, Isolated from a Marine Shallow Hydrothermal Vent in Taiwan

Abstract: A new extremely thermophilic, anaerobic, gram-negative bacterium, strain NTOU1, was enriched and isolated from acidic marine hydrothermal fluids off Gueishandao island in Taiwan with 0.5% starch and 0.5% maltose as carbon sources. This strain was capable of growth utilizing various sugars found in lignocellulosic biomass as well as xylan and cellulose, and produced ethanol, lactate, acetate, and CO 2 as fermentation products. The results of a 16S rRNA gene sequence analysis (1,520 bp) revealed NTOU1 to belong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Thermoanaerobacterium saccharolyticum strain NTOU1, a Gram-negative thermophilic bacterium, was isolated from shallow marine hydrothermal vents off Gueishandao Island in Taiwan. Strain NTOU1 is of particular interest, because it has been reported that among wild-type anaerobic thermophilic ethanogens, this strain had the highest ethanol yield rate ( 5 ). Here, we attempted to sequence, assemble, and annotate the draft genome sequence of NTOU1.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Thermoanaerobacterium saccharolyticum strain NTOU1, a Gram-negative thermophilic bacterium, was isolated from shallow marine hydrothermal vents off Gueishandao Island in Taiwan. Strain NTOU1 is of particular interest, because it has been reported that among wild-type anaerobic thermophilic ethanogens, this strain had the highest ethanol yield rate ( 5 ). Here, we attempted to sequence, assemble, and annotate the draft genome sequence of NTOU1.…”
Section: Genome Announcementmentioning
confidence: 99%
“…For example, genera Thermoanaerobacter or Thermoanaerobacterium were detected in deep terrestrial environments such as terrestrial deep crusts (Szewzyk et al, 1994;Liu et al, 1997;Roh et al, 2003;Zhang et al, 2006), deep oil reservoirs (e.g., L'Haridon et al, 1995;Slobodkin et al, 1999;Birkeland, 2004;Fardeau et al, 2004), and terrestrial hot springs that serve as channels between the deep, hot biosphere and the surface biosphere (Cook et al, 1996;Slobodkin et al, 1999;Bao et al, 2002;Wagner and Wiegel, 2008;Bonch-Osmolovskaya, 2010). However, despite quite a few other types of thermophilic metal-reducing bacteria detected (e.g., Slobodkin, 2005), genera Thermoanaerobacter and Thermoanaerobacterium have rarely been reported from deep-sea hydrothermal vents where diverse thermophilic microorganisms thrive (e.g., Parkes et al, 1994;Reysenbach et al, 2000;Sokolova et al, 2001;Holden and Adams, 2003;Huber et al, 2007;Nakagawa and Takai, 2008;Wagner and Wiegel, 2008;Tsai et al, 2011). All these geological and microbial ecological observations suggest that Fe(III) respiration is the key component of the deep, hot biosphere (Gold, 1992;Kashefi and Lovley, 2003).…”
Section: Application To the Rapid Detection Of Biogenic Magnetite In mentioning
confidence: 99%
“…Generally, we use laborious culturing techniques with specific apparatuses ( e.g. , roll tube and agar shake tube) for isolation of the methanogens as well as other obligate anaerobic microbes to eliminate oxygen in the culture medium (8, 21, 30, 31). Such obstacles have led to the difficulty in isolation of obligate anaerobic microorganisms.…”
mentioning
confidence: 99%